A left shift in the oxyhaemoglobin dissociation curve in patients with severe coronavirus disease 2019 (COVID‐19) - Vogel, Dominik J. (Br J Haematol, 2020)
Critically ill patients with coronavirus disease 2019 (COVID‐19) present with hypoxaemia and are mechanically ventilated to support gas exchange. We performed a retrospective, observational study of blood gas analyses (n = 3518) obtained from patients with COVID‐19 to investigate changes in haemoglobin oxygen (Hb–O(2)) affinity. Calculated oxygen tension at half‐saturation (p(50)) was on average (±SD) 3·3 (3·13) mmHg lower than the normal p(50) value (23·4 vs. 26·7 mmHg; P < 0·0001). Compared to an unmatched historic control of patients with other causes of severe respiratory failure, patients with COVID‐19 had a significantly higher Hb–O(2) affinity (mean [SD] p(50) 23·4 [3·13] vs. 24·6 [5.4] mmHg; P < 0·0001). We hypothesise that, due to the long disease process, acclimatisation to hypoxaemia could play a role.